Putusan MK Atas Pengujian Formil Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Yanti, Rizka Fitri; Dalimunthe, Dermina (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The problem in this research is related to the Constitutional Court Decision Number 91/PUU-XVIII/2020 on the Review of Law Number 11 of 2020 concerning Job Creation. This type of research is library research through a normative juridical approach. The data sources used are primary and secondary legal materials. Primary legal materials consist of the Constitutional Court Decision Number 91/PUU-XVIII/2020, Law Number 24 of 2003, Law Number 12 of 2011). While secondary legal material includes official documents consisting of scientific articles, books, journals. Data collection techniques in this study were case study and documentation methods. Furthermore, the data analysis technique used in this study is qualitative analysis that is collecting secondary and primary legal materials on the Constitutional Court's decision related to the problem being studied. The results of this study state that the review of Law Number 11 of 2020 concerning Job Creation refers to the provisions of Law Number 12 of 2011 concerning Formation of Legislation. In the process of its formation it did not apply the principles of forming good laws, including not applying the principle of transparency. So that it does not provide space for participation for the public to participate in discussing the law. The consideration of the Constitutional Court judges in composing the decision is the consideration of justice through Conditional Unconstitutional. Then the legal consequences of the formation of the Job Creation Law included cutting severance pay, termination of employment, no maternity leave and miscarriages for women workers.